Synthesis, Electrochemical, Thermodynamic, and Quantum Chemical Investigations of Amino Cadalene as a Corrosion Inhibitor for Stainless Steel Type 321 in Sulfuric Acid 1M - Y. Koumya; R. Idouhli; A. Oukhrib; M. Khadiri; A. Abouelfida; A. Benyaich (International Journal of Electrochemistry)
The corrosion of stainless steel is one of the major industries’ issues that gained wide interest among researchers. It became necessary to develop and apply eco-friendly approaches to corrosion control. This work explores the inhibitory effect of a newly synthesized amino cadalene (ACM) on the corrosion of stainless steel type 321 in sulfuric acid 1M. Particularly, the experimental study consisting of electrochemical and surface analyses was conducted in conjunction with a theoretical approach. The electrochemical results showed that ACM acted as a mixed-type corrosion inhibitor and the inhibition efficiency attained 91% at 10−3M. EIS measurements revealed that both metal charge transfer and diffusion processes are involved in the interfacial metal/solution reactions. The interfacial mechanism is thoroughly investigated; the physisorption of the protonated molecules was preceded by the formation of a negative layer due to adsorption of the solution anionic species. The experimental insights are corroborated with the quantum chemical calculations.